The Influence of Stress Level and Resilience on The Performance of Health Workers at RSIA Aisyiyah Pekajangan - Rahman, Aulia; Nurwijayanti, Nurwijayanti (Syntax Corporation, 2024)
A health worker must be able to balance various stressors obtained in the work environment because they have to provide professional services to patients. This requires personal factors that are inherent in nurses so that they are able to adapt to stressful conditions. Internal factors include the ability to withstand problems (resilience). The purpose of this study to determine and analyze the influence of stress levels and resilience on the performance of RSIA Aisyiyah Pekajangan health workers. This research is a quantitative research with a cross-sectional method. A sample of 129 respondents was obtained using Simple Random Sampling. After filling in informed consent, respondents filled out stress level questionnaires, resilience and performance questionnaires. After that, data processing and analysis was carried out using SPSS. The calculated F value is 10.642 > F table 3.91 and the sig is 0.000 < 0.05. From these results it can be said that simultaneously, the variables stress level (X1) and resilience (X2) influence the performance variable (Y). In the multiple liner regression test, the result was Y = 17.469+ 0.081X1 + 0.095X2 + e. The level of stress and resilience has a significant effect on the performance of health workers.